2013
DOI: 10.1007/s11746-013-2344-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Conjugated Linoleic Acid‐Rich Soy Oil

Abstract: CLA-rich soy oil (CLARSO) has been produced by linoleic acid isomerization in soy oil TAG. The objective was to determine the physicochemical properties of the novel CLARSO relative to conventional refined bleached deodorized soy oil (RBDSO). Iodine value decreased in CLARSO samples despite unsaturation being unchanged, probably because conjugated double bonds in triacylglycerol (TAG) of CLARSO impede the complete addition of iodine. Thermal analysis by differential scanning calorimetry showed the melting poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, the CLA-rich shortenings also have a higher SFC (% SFC) as well as higher latent heat of crystallization and melting than the soy oil controls indicating a comparatively higher crystalline fraction. Thus, CLARSO produced firmer shortenings than did Ruan and Proctor [13] found that CLARSO had a higher melting temperature and viscosity than refined, bleached, deodorized (RBD) soy oil. These differences were attributed to greater intermolecular hydrophobic interaction forces of the CLA conjugated double bonds in the transtrans fatty acids of CLARSO.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, the CLA-rich shortenings also have a higher SFC (% SFC) as well as higher latent heat of crystallization and melting than the soy oil controls indicating a comparatively higher crystalline fraction. Thus, CLARSO produced firmer shortenings than did Ruan and Proctor [13] found that CLARSO had a higher melting temperature and viscosity than refined, bleached, deodorized (RBD) soy oil. These differences were attributed to greater intermolecular hydrophobic interaction forces of the CLA conjugated double bonds in the transtrans fatty acids of CLARSO.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, triplicate control, soy control, and CLA-rich eggs containing the highest dietary CLA concentration were analyzed in duplicate after 5 and 10 days of refrigerated storage [ N = 18]. An AR-2000 Rheometer was used for viscosity analysis . Each yolk sample was vortexed for 20 s and 2 aliquots of yolk were dispensed from a 1 mL auto pipet on the lower rheometer plate.…”
Section: Methodsmentioning
confidence: 99%
“…An AR-2000 Rheometer was used for viscosity analysis. 19 Each yolk sample was vortexed for 20 s and 2 aliquots of yolk were dispensed from a 1 mL auto pipet on the lower rheometer plate. A 40 mm diameter sand-blasted geometry was applied to the sample surface at a constant shear rate of 100 s −1 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…There is no research available on CLA-rich oil use in salad dressing preparation. However, the greater viscosity that CLA-rich oil experiences at refrigerator temperatures, relative to conventional soybean oil (Ruan & Proctor 2014), may be useful in salad oil and refrigerated sauces to enable suspension of particles and maintain a richer, thicker texture.…”
Section: Dressings the Main Ingredient Of Numerous Salad Dressings An...mentioning
confidence: 99%